Theoretical and practical aspects of pedagogy and psychology - Rodzin S. I., Bova V. V., Koniushenko S. M., Pechalova L. V., Pechalov A. K., Belousova L. V., Glotova G. A., Glotova G. A., Glotova G. A., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Liakhova E. G., Pimenova L. G., Tsaregorodtseva O. S., Sapegin V. A., Koreneva A. V., Kochanovskaia D. K., Podgornova N. A., Kazakevich A. V. (Theoretical and practical aspects of pedagogy and psychology, 2024)
the chapter is devoted to the study of some aspects of research activities among medical university students. This topic is very relevant in view of the fact that processes of optimization and modernization are currently taking place in Russia, both of medicine in general and of medical education itself. Taking into account the fact that our country lacks qualified medical workers who would be engaged in scientific activities, there is a constant development of new programs and disciplines aimed at providing students with basic concepts about research activities, methods and options for its conduct. Such disciplines at VSMU named after. N.N. Burdenko became: «organization, conduct and registration of scientific research results in experiments and clinics» on the basis of the Department of Operative Surgery with Topographic Anatomy and «statistical processing of scientific results» on the basis of the Department of Healthcare Management. The purpose of the work was an attempt to evaluate some aspects of both the research work of students in general, and aspects related to the training of students in the above disciplines. The basis of the work was a questionnaire specially developed by the authors, containing a number of questions concerning the attitude towards students’ research activities, awareness of the advantages of conducting such activities, as well as an analysis of some aspects of the learning process when studying the above disciplines. The work is of interest not only to ordinary higher education teachers, but also to those teachers who are involved in the educational process at the university.
Keywords: дисциплина; студент; аспект; научная деятельность; student; scientific activity; discipline; aspect